From the Mainframes to the Masses: A Participatory Computing Movement in Minnesota Education. - Rankin, Joy (Information & Culture, 2015)
Historians have demonstrated how systems like Usenet and Minitel fostered the social practices that we now associate with the TCP/IP Internet, but no one has considered networked computing in education. From 1965 to 1975, Minnesota implemented interactive computing at its public schools and universities with time-sharing systems--networks of teletypewriter terminals connected to computers via telephone lines. These educational networks, created with different priorities from military-sponsored networks, were user oriented from die start and encouraged software sharing and collaboration. Focusing on die educational setting gives us a history of the Internet firmly grounded in the social and political movements of the long 1960s.